Review: Will “cultured meat” transform our food system towards more sustainability? - Jean-François Hocquette; Sghaier Chriki; Dominique Fournier; Marie-Pierre Ellies-Oury (Animal)
Our agri-food system today should provide enough healthy food of good quality for the growing human population. However, it should also preserve natural resources and better protect livestock. In this context, some FoodTech companies are developing a disruptive approach: cell culture for in vitro food production of “meat” but this technology is still at the research and development stage. This article will highlight its development, the technologies used and the stakeholders involved (Part 1), its potential environmental impacts (Part 2) but also regulatory, social and ethical issues (Part 3). This article aims to shed light throughout the manuscript on two major controversies related to “cultured meat”. The first controversy is related to its ethical aspects, which includes different points: its potential to reduce animal suffering and therefore to improve animal welfare, the future values of our society, and a trend towards food artificialisation. The second controversy includes environmental, health and nutritional issues, in relation to the characteristics and quality of “cultured meat” with an important question: should we call it meat? These two controversies act in interaction in association with related societal, legal and consequently political issues. Answers to the various questions depend on the different visions of the World by stakeholders, consumers and citizens. Some of them argue for a moderate or a strong reduction in livestock farming, or even the abolition of livestock farming perceived as an exploitation of farm animals. Others just want a reduction of the current much criticised intensive/industrial model. Compared with other potential sustainable solutions to be implemented such as reduction of food losses and waste, new food consumption habits with less proteins of animal sources, sustainable intensification, development of agroecological livestock production, or the development of the market for other meat substitutes (proteins from plants, mycoproteins, algae, insects, etc.), “cultured meat” has an uncertain future.